Algorithm for professional communication in medical settings - Bezsheiko, Vitaliy; Davydenko, Inna (Psychosomatic Medicine and General Practice, 2017)
This is a short algorithm for professional communication in specific clinical situations. Recommendations are developed on the basis of the guidelines on objective structured clinical examination. It is an educational material, intended for medical students and physicians, who have just started a clinical practice.